Atividade antimicrobiana, elaboração de escalas diagramáticas, caracteres agronômicos e manejo de doenças em milho por produtos à base de cálcio, cobre, manganês e zinco - Lorenzetti , Eloisa (2019)
The objective of this study was to verify whether chelated products based on calcium, copper, manganese and zinc inhibit the spores germination of Pucciniasorghi, Cercospora sp. and Exserohilumturcicum, if they have capacity to manage Pantoeaananatis, Pucciniapolysora, Cercosporazeaemaydis, E.turcicum, Diplodiamacrospora and Pseudomonas avenae in first seasoncorn, and in the management of P.ananatis, P.polysora and C.zeaemaydis in second seasoncorn, as well as if it can interfere in agronomic traits. Additionally, diagrammatic scales were developed and validated to quantify the severity of leaf spot caused by D. macrospora fungus and leaf bacterial spot in maize caused by P. avenae. The treatments were commercial chelates of amino acids with the elements calcium 15%, copper 5%, manganese 15% and zinc 10%, at the doses of 0.5 kg ha-1, 0.3 L ha-1, 0.4 kg ha-1 and 1 L ha-1, respectively; a treatment with fungicide (20% azoxystrobin and 8% ciproconazole at the dose of 0.3 L ha-1 + 25% propiconazole at the dose of 0.4 L ha-1); and a treatment with water. In vitro tests were performed using spores and treatments at the same time (zero) and 1, 2, 3, 4 and 5 hours after the addition of the spores. In vivo trials of first and second crops were performed in the field for two consecutive years using two simple hybrids, and evaluating the agronomic traits: plant height, stalk diameter, number of rows per spike, number of grains per row, productivity and mass of a thousand grains, as well as the severity of leaf diseasesusing diagrammatic scale or severity notes. For the first season, the chemical analysis of the leaves was also carried out. For the diagrammatic scales, leaves with different levels of disease severity were collected and the total leaf area and the injured area of the middle third were measured determining the minimum and maximum limits of the disease. For both, the validation was performed by eight evaluators, four inexperienced and four experienced. In the in vitro tests, in the simultaneous application of the treatments and spores, the chelates presented a mean reduction of 39%, both for spores germination of P. sorghi and Cercosporasp. These same pathogens showed a mean reduction of 52%, 59%, 77%, 87%, 81% and 64% forP. sorghi and 40%, 33%, 17%, 18%, 4% and 2% forCercospora sp., in the times, zero, 1, 2, 3, 4 and 5 hours after treatment, respectively. There was no inhibitory effect for E. turcicum. In vivo, in the first crop 2016/2017 for the variables number of rows per ear and number of grains per row, the fungicide presented the highest values, and for the variables thousand-grain mass and productivity, the chelates did not differ from the fungicide and were other than water. In the first season 2017/2018 for one thousand grain mass and productivity, only the fungicide increased significantly. In both the first harvests there was no significant effect of chelates for the evaluation of disease severity and for the elements tested, and there was no difference in the nutrient content before and after foliar application. In none of the years studied for the second season, significant effect of chelates was recorded for agronomic traits and for the diseases severity. For leaf spot caused by fungus D.macrospora, the proposed diagrammatic scale presented six levels of severity: 0,5%; 3%; 8%; 23%; 36% and 55%, and for the bacterial spot of the leaf were: 1,5%, 2,5%, 9%, 18%, 46% and 70%. The products may influence agronomic traits in the first season, with no influence on the second season. For the first and second harvests, there was no influence on the severity of the diseases evaluated in corn in hybrids and under the edaphhoclimatic conditions in which the study was conducted. There was an improvement in the accuracy and precision of the evaluators when using the proposed diagrammatic scales.